(untitled) (Conference on English Language Teaching, 2023)
The failure when the students are trying to speak in another language sometimes cannot be denied. This case can cause many misunderstanding in pragmatic aspects. We are as the teachers are obliged to guide them to solve their difficulties in interacting with other speakers from different background and culture. We call this case as pragmatic failure since the pragmatic itself also talks about cross-cultural communication. Therefore, it is a necessary for foreign language learners to deepen their knowledge about cross-cultural pragmatic or intercultural pragmatic awareness. But unfortunately, it is quite a big job for teachers to teach the ESL learners along with the culture. The teachers need to choose what culture that they should apply in classroom since language and culture are inseparable. This article is aimed to explore about the cross-cultural pragmatic failure and cross-cultural pragmatics awareness.